In Situ Glycine-nitrate Combustion Synthesis of Ni-La/SiO2 Catalyst for Methane Cracking - Mazni, Ismail; Mohamad Muzakkir, Tajuddin; Asmida, Ideris (American Chemical Society (ACS Publications), 2019)
Ni–La catalyst supported on SiO2 (Ni–La/SiO2) synthesized using in situ glycine–nitrate combustion was analyzed for catalyst dispersion at various catalyst-to-support ratios and support surface areas. Catalytic activity of the catalyst was assessed for methane cracking. The catalyst with higher support loading had a better catalyst dispersion. The use of a support with high surface area also improved catalyst dispersion. Ni–La/SiO2 B synthesized using a support with high surface area have a higher catalyst dispersion than that of Ni–La/SiO2 A with a support of low surface area. As a result, Ni–La/SiO2 B had a better methane conversion (the maximum of ∼60%) than that of Ni–La/SiO2 A (∼40%) and offered a higher H2 yield. Moreover, Ni–La/SiO2 B was found to be active for carbon formation. Nevertheless, the catalyst remained catalytically active for methane cracking without deactivation.